Is there a union wage premium in Germany and which workers benefit most? - Marina Bonaccolto-Töpfer; Claus Schnabel (Friedrich-Alexander-Universität Erlangen-Nürnberg, Lehrstuhl für Arbeitsmarkt- und Regionalpolitik, 2023)
Using representative data from the German Socio-Economic Panel (SOEP), this paper finds a statistically significant union wage premium in Germany of almost three percent which is not simply a collective bargaining premium. Given that the union membership fee is typically about one percent of workers' gross wages, this finding suggests that it pays off to be a union member. Our results show that the wage premium differs substantially between various occupations and educational groups, but not between men and women. We do not find that union wage premia are higher for those occupations and workers which constitute the core of union membership. Rather, unions seem to care about disadvantaged workers and pursue a wider social agenda. – – Mit repräsentativen Daten des Sozio-oekonomischen Panels findet diese Studie für Deutschland eine statistisch signifikante Lohnprämie von fast drei Prozent, die mit einer Gewerkschaftsmitgliedschaft einhergeht, aber keine Tarifvertragsprämie ist. Da der Gewerkschaftsbeitrag üblicherweise bei ungefähr einem Prozent des Bruttoverdienstes liegt, zahlt es sich also aus, Gewerkschaftsmitglied zu sein. Unsere Ergebnisse zeigen, dass die gewerkschaftliche Lohnprämie stark zwischen verschiedenen Berufen und Bildungsgruppen variiert, allerdings nicht zwischen Männern und Frauen. Wir finden nicht, dass diese Lohnprämie für diejenigen Berufe und Arbeitskräfte höher ausfällt, die den Kern der gewerkschaftlichen Mitglieder darstellen. Vielmehr scheinen sich Gewerkschaften um benachteiligte Arbeitskräfte zu kümmern und eine breitere soziale Agenda zu verfolgen.
Keywords: J31; J53; 330; union wage premium; collective bargaining; union membership; Germany